Kejahatan Money Laundering dan Lembaga Perbankan - Aroma Elmina Martha (Universitas Islam Indonesia, 2001)
Money laundering is regarded as one of the very serious white-collar crimes in this country is. A lot of people are involved in the debate on this topic, and nowadays people in this country are in the big spirit to always criticize every single aspect of the law enforcement in this case. This because, as has been commonly understood, money laundering happens is huge number of money. To be sure, the ratification of U.N. Convention Against Illicit Trafficking in Narcotic Drugs arid Psychotropic Substances 1988 gives promise to diminish this kind of crime.